Власні торгові марки в роздрібній торгівлі - Удянська, Галина Михайлівна; Чернобровкіна, Світлана Віталіївна (НТУ "ХПІ", 2014)
В статті проаналізовано загальні тенденції розвитку власних торговельних марок українських роздрібних мереж, визначено, що розробка і виведення на ринок приватних марок представляється найбільш економічним рішенням у сучасних умовах. Перелічено українські торговельні мережі, їх власні торгові марки, а також надано частку продукції ВТМ у валовому доході мережі. Визначено переваги та недоліки виробництва private label для виробника.

The paper analyzes the general trends of own brands Ukrainian retailers determined that develop and bring to market private label is the most economical solution in the modern world. Ukrainian retailers listed their own brands, given the proportion of own brands in the gross income of the network, and year of establishment and format of store. There is no clearly defined way of Private Label in Ukraine. Many networks own portfolio of trademarks balanced, and in some - combined set. Some of them - Private Label develop only in the "most interesting" category. There are networks that develop Private Label in all categories, but this limiting case. Formulated the benefits of production of goods under private brand to brand owner. Advantages and disadvantages of private label production for the manufacturer. Quality products should be a major tool in the fight for customer loyalty. In addition, mandatory cost optimization. Conclusions regarding the further development of its own brands. Provided recommendations to owners of commercial networks for effective promotion of their own brands.
Private labels in retailers
Keywords: жорстка конкуренція; торговельні мережі; споживачі; приватні марки; private label; retailer; consumer; manufacturer